On Temperature-Dependent and Spatially Structured Dengue Transmission Models: A Mathematical Review - Abdullahi Abdu; Admi Nazra; Arrival Rince Putri; Mahdhivan Syafwan (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2026)
Dengue fever remains a major public health concern in tropical and subtropical regions, where transmission dynamics are strongly influenced by environmental variability and human mobil ity. Mathematical modelling provides a rigorous framework for capturing these interactions and informing effective control strategies.This review presents recent advances in deterministic and spatially structured dengue transmission models that incorporate temperature-dependent parameters and human mo bility. Emphasis is placed on compartmental formulations, including multi-patch and meta population models, where movement between regions plays a key role in disease spread. The influence of temperature on key epidemiological parameters, such as mosquito biting rates, development rates, and survival probabilities, is examined through nonlinear functional relationships.In addition, common analytical approaches are discussed, including the derivation of the basic reproduction number, stability analysis of equilibria, and sensitivity analysis. The integration of control strategies within these frameworks is also reviewed, demonstrating how intervention policies can be evaluated under varying environmental and mobility conditions.Overall, the review highlights the importance of combining environmental and spatial effects to better understand dengue transmission and support adaptive control strategies.